Men, Masculinity and Violence: a critical engagement of Pentecostal Men’s Conference promotional material - Ngcobo, Siwakhile; Van Der Walt, Charlene (Sacrilegens, 2024)
The promotional media material for men’s conferences and the crisis of Gender Based Violence in South Africa formed the basis of this study exploring the production of masculinity in Pentecostal men’s conference promotional material at the backdrop of Gender Based Violence (GBV). Within research in general but specifically when it comes to theological or religious reflection, the way in which masculinity construction and production has been understood in relation to GBV has been underrepresented. Research has shown that heteropatriarchal ideologies of masculinity perpetuate hegemonic masculinity, contributing to the high rate of gendered pandemics in Africa. Using digital methodology, a study was conceptualised to explore masculinity production in men’s conference promotional media material and the effect it has in mitigating the scourge of GBV in the South African context. The media material was analysed using critical visual analysis and framed under feminist and mediatization frameworks. This contribution offers a critical engagement of Pentecostal men’s conference promotional material arguing that the production and representation of masculinity is problematic. It argues that discourses of power and dominance that are prevalent in the promotional material puts women and other men in a vulnerable position of experiencing violence. It further contends that masculinity production promoted in the promotional material sustains violence and reinforces hegemonic norms of masculinity within the Christian faith landscape. Keyword: Masculinity. Power. Dominance. Promotional. Pentecostalism.